Comparison of the Intensity of Postoperative Pain Between Open and Laparoscopic Access of Ventral Hernioplasty with IPOM (Intraperitoneal Onlay Mesh) Technique - Kadri Edjevit; Panikj Katarina; Mladenovic Dragoslav; Jota Gjorgji; Nanceva Jasminka; Antovikj Svetozar; Lazova, Evgenija (My University, 2020)
Introduction: Despite the numerous advantages of laparoscopic ventral hernioplasty over the open access hernioplasty, described in the literature, the general clinical experience is that patients have severe pain in the first few days, hence early postoperative pain is a challenge in this procedure.The aim of this study was to compare early postoperative pain and whether there was statistically significant difference in the intensity of postoperative pain among patients operated with open and laparoscopic approach with IPOM hernioplasty during resting and activity.Material and methods: A randomized, prospective, comparative study was performed on 63 patients who met the inclusion criteria, operated with the IPOM technique and divided into two groups: open access in 32 patients and laparoscopic approach in 31 patients. In both groups, postoperative pain was compared at eight time intervals during rest and activity, quantified using VAS. The statistical processing and analysis of the data was done in the statistical programme SPSS version 23.0.Results: The results of the study showed that at rest and activity, patients in both groups had significantly different pain intensities on the day of the intervention, the first and second day after the intervention (p<0.0001). At these time points, the intensity of pain was significantly stronger in patients undergoing laparosopic hernioplasty. On the third and seventh postoperative days, as well as one and six months after the intervention, there was no significant difference in pain intensity between the two methods during rest and activity.Discussion: The general clinical experience confirmed in our study is that patients after laparoscopic ventral hernioplasty suffer from severe pain in the early postoperative period and it is the biggest challenge and problem after these operations. The explanation is that it is the result of transfascial sutures for mesh fixation in both groups and additionally multiple lesions of the parietal peritoneum in the laparoscopic method due to the numerous fixations of the mesh with tackers. Future research should focus on developing new non-traumatic methods for mesh fixation (Fibrin Glue) and studies that will analyse in detail the impact of postoperative pain on quality of life.
Keywords: Laparoscopic IPOM technique; open IPOM technique; absorbable tackers; transfascial sutures; postoperative pain.